New art gallery set for opening (Raton Range Raton, NM, 1989)
This article is about Old Pass Gallery grand opening.
Newspaper article
Master list item #: 138
File location is in the Raton file Cabinet
Keywords: Cornay, Dino -- Artist; Old Pass Gallery; Raton Arts and Humanities Council; Art Shows; Art Exhibits; Artist; Gallery Openings; Raton, New Mexico